Expression of angiopoietic factors in normal and type-I diabetes human placenta: a pilot study - Janota, Jan; Pomyje, Jirí; Toth, Dusan; Sosna, Ondrej; Zivný, Jaroslav; Kuzel, David; Stranák, Zbynek; Necas, Emanuel; Zivný, Jan H (European journal of obstetrics, gynecology, and reproductive biology, 2003)
OBJECTIVES: Morphological changes of blood vessel wall have been described in placenta from pregnancies complicated by diabetes mellitus type-I. STUDY DESIGN: We measured mRNA expression of vascular endothelial growth factor (VEGF), angiopoietin 1 and 2 (Ang-1 and Ang-2), their receptors VEGFR-1, VEGFR-2, Tie-2, fibroblast growth factor 2 (FGF-2), and its receptor FGF-2R in placental tissue of diabetes type-I patients, in normal term placenta, and endometrium of non-pregnant women by real time reverse transcriptase PCR. RESULTS: The expression of Ang-2 and VEGFR-1 mRNAs was significantly higher in placenta (P<or=0.01). The expression of VEGF and VEGFR-2 mRNAs was significantly lower in normal term or diabetes type-I placenta compared to human endometrium (P<or=0.01). We did not detect a significant difference in the expression of Ang-1, Ang-2, Tie-2, VEGF, VEGFR-1, VEGFR-2, FGF-2, and FGF-2R in normal and diabetes type-I placenta. CONCLUSION: These data show differential expression of Ang-2, VEGFR-1, VEGF, and VEGFR-2 in placenta and endometrium. The expression of Ang-1, Ang-2, Tie-2, VEGF, VEGFR-1, VEGFR-2, FGF-2, and FGF-2R was not different in normal and type-I diabetes placenta.
Keywords: placenta; Fibroblast Growth Factor 2; messenger RNA; tyrosinkinasové receptory; receptory fibroblastových růstových faktorů; angiopoetin-1; Angiopoietin-2; Pregnancy in Diabetics; RNA, Messenger; fibroblastový růstový faktor 2; těhotenství při diabetu; Pregnancy; exprese genu; Placenta; Humans; Angiopoietins; Reverse Transcriptase Polymerase Chain Reaction; Vascular Endothelial Growth Factor Receptor-1; receptor 2 pro vaskulární endoteliální růstový faktor; Receptor, Fibroblast Growth Factor, Type 2; diabetes mellitus 1. typu; Female; Vascular Endothelial Growth Factor Receptor-2; angiopoetiny; polymerázová řetězová reakce s reverzní transkripcí; Gene Expression; receptor TIE-2; ženské pohlaví; Angiopoietin-1; Receptor, TIE-2; Diabetes Mellitus, Type 1; Receptors, Fibroblast Growth Factor; angiopoetin-2; Vascular Endothelial Growth Factor A; receptor 1 pro vaskulární endoteliální růstový faktor; receptor fibroblastových růstových faktorů, typ 2; těhotenství; Receptor Protein-Tyrosine Kinases; vaskulární endoteliální růstový faktor A; lidé